Book citation index: A proposal of best practices for publishers - Aguillo, Isidro F. (Anuario ThinkEPI, 2013)
The presentation of the Book citation index, the new tool for bibliometric assessment of the ISI / Thomson Reuters, has generated deep concern about its inclusion criteria that perpetuate the biases of the citations databases already produced by this company. Given the importance this product may have for the description of scientific activity in disciplines such as social sciences and humanities, we propose a series of recommendations for book publishers with the aim of promote the indexation of their works in this database. A key proposal is to group the books in collections and then to build series in a similar fashion to scientific periodicals. Following this procedure and for guarantying formal quality, it is suggested to set up international committees for the collections, reviewers for each individual title, and additional information that can be added to the database like authors affiliation, extended summary, at least in English, keywords or the cited bibliography following international standards. As a final recommendation it is proposed the open access through any available channels.